Final answer:
The first step to solve the system of equations using substitution is to solve the first equation for x. Then, substitute this expression into the second equation to find the value of y.
Step-by-step explanation:
The first step to solve the system of equations using substitution is to solve the first equation for x.
To do this, we will isolate x by adding y to both sides of the equation:
X - y = -1
X = y - 1
Now that we have solved the first equation for x, we can substitute this expression into the second equation to find the value of y.
Substituting y - 1 for x in the second equation:
2(y - 1) - y = 3
2y - 2 - y = 3
y - 2 = 3
y = 5
Now that we have the value of y, we can substitute it back into the first equation to find the value of x:
X - 5 = -1
X = 4
So the solution to the system of equations is x = 4 and y = 5.